Indirect tolerability comparison of Deutetrabenazine and Tetrabenazine for Huntington disease - Claassen, Daniel O. (J Clin Mov Disord, 2017)
BACKGROUND: Vesicular monoamine transporter 2 (VMAT2) inhibitors can improve hyperkinetic movements, and are effective treatment options for chorea of Huntington disease (HD). Tetrabenazine was assessed for treating chorea in the TETRA-HD trial, and while efficacious, there are tolerability concerns possibly due to its pharmacokinetic properties. Deutetrabenazine is a novel VMAT2 inhibitor that contains deuterium, which extends active metabolite half-lives and minimizes drug concentration fluctuations. In the First-HD trial, deutetrabenazine was efficacious in treating chorea and was generally well tolerated. In the absence of a head-to-head trial, we performed an indirect treatment comparison (ITC) of the tolerability of deutetrabenazine and tetrabenazine for the treatment of HD-associated chorea, as observed in the First-HD and TETRA-HD trials, using well-established comparison methods. METHODS: Data from the Phase III, 12-week, parallel-group, clinical trials First-HD (N = 90) and TETRA-HD (N = 84) were used to conduct an ITC of the tolerability of deutetrabenazine versus tetrabenazine using two anchor-based methods: Bucher comparison for unadjusted ITCs, and matching indirect comparison for adjusted ITCs. Overall adverse events (AEs; mild, moderate, and severe), serious AEs, specific AEs occurring in ≥10% of patients, and discontinuations (all-cause and AE-related) were included in the analysis. The risk differences of these outcomes for deutetrabenazine and tetrabenazine were estimated by subtracting the applicable placebo-adjusted risk in First-HD from that of TETRA-HD. Sensitivity analyses were performed to address differences between trials, and p-values were obtained from z-tests. RESULTS: Compared with tetrabenazine, deutetrabenazine was associated with a significantly lower risk of moderate to severe AEs and neuropsychiatric AEs including agitation, akathisia, depression, depression/agitated depression, drowsiness/somnolence, insomnia, and parkinsonism in both adjusted and unadjusted analyses (p < 0.05 for each). Deutetrabenazine had a significantly lower rate of dose reduction or dose reduction/suspension in the unadjusted and adjusted analyses (p < 0.001 for each). Deutetrabenazine resulted in numerically more mild AEs, such as diarrhea and coughing; however, these results were not statistically significant. CONCLUSIONS: This indirect treatment comparison demonstrates that for the treatment of HD chorea, deutetrabenazine has a favorable tolerability profile compared to tetrabenazine. TRIAL REGISTRATION: ClinicalTrials.gov NCT01795859 and NCT00219804.